Syzygium gratum Extract Alleviates Vascular Alterations in Hypertensive Rats - Pakdeechote, Poungrat (Medicina (Kaunas), 2020)
Background and Objectives: Syzygium gratum (SG) is a local vegetable and widely consumed in Thailand. Previously, a strong antioxidative effect of SG extract has been reported. The effects of SG extract on hypertension have remained unknown. The effect of SG aqueous extract on blood pressure and vascular changes were examined in L-NAME-induced hypertensive rats (LHR), and its potential active constituents were also explored. Materials and Methods: Male Sprague Dawley rats were allocated to control, L-NAME (40 mg/kg/day), L-NAME + SG (100, 300, 500 mg/kg/day), or captopril (5 mg/kg/day) groups. The components of SG extract were analyzed. Results: The analysis of aqueous SG extract was carried out using HPLC-Mass spectroscopy, and phenolic compounds could be identified as predominant components which might be responsible for its antihypertensive effects observed in the LHR model (p < 0.05). Additionally, SG extract also improved vascular responses to acetylcholine and decreased vascular remodeling in LHR (p < 0.05). Enhancements of eNOS expression and plasma nitric oxide metabolite levels, and attenuation of angiotensin converting enzyme (ACE) activity and plasma angiotensin II levels were observed in the LHR group treated with SG. Moreover, SG exhibited strong antioxidant activities by reducing vascular superoxide generation and systemic malondialdehyde in LHRs. Captopril suppressed high blood pressure and alleviated vascular changes and ACE activity in LHRs, similar to those of the SG extract (p < 0.05). Conclusion: Our results suggest that the SG extract exhibited antihypertensive effects, which is relevant to alleviation of vascular dysfunction and vascular remodeling of LHRs. These effects might be mediated by phenolic compounds to inhibit ACE activity and scavenge reactive oxygen species in LHR.